RESTRICCIONES EN EL ACCESO AL MERCADO DE VALORES DEL PERÚ - Mauricio Pachas, Pablo Willins (2012)
The present article is extracted from the Thesis “structural Deficiencies of the offer of financial assets on the stock market of Peru” authored by the undersigned and it shows the principal reasons of the lack of financial instruments that originates excess of liquidity on the stock market, causing capital emigration, such as AFP that have to be invested abroad. The study raises the question Why is there a deficit of financial assets in the stock market in Peru? leading to our hypotheses: “ The deficient regulation and promotion of the Stock market of Peru contracts the access of the companies to this market “ confirmed with the results of the applied survey. In its development highlights is outlined small participation of companies offering financial instruments in the stock market, described by some 220 companies by 2010 and if we consider mutual funds amount, to 263 companies. Although the analysis has determined that there is a universe of 913 large companies with economic and financial conditions required by that market demand, Only 144 big companies are involved, that is 16 % of the total, determining that 769 big companies are absent of the stock market. On the other hand, it is found that the governing law increases the price of the cost of emission of bonds and actions, due to the high steps in the process of structure, legal expenses, registration, sorting, etc. which causes high cost of emissions, being more than 3% of cost required for emission of 5 million dollars for bonds. Such restrictions on market access are based in the queries and answers applied to the big companies that do not take part, those who have demonstrated in a level of 37 %, would be encouraged to enter the market with more flexible and emissions requirements and cost reduction. Likewise there is established the need to adopt actions and economic measures not of legal character but of markets, to stimulate the access to the market of more companies, in order to increase the supply of trading financial instruments of negotiation (titles-values) significantly, strengthening the approach of competitive market by Regulation of today Superintendence of the Stock market.